Effect of age and gender on children’s reading performance: The possible neural underpinnings - Filippos Vlachos; Artemis Papadimitriou (Cogent Psychology, 2015)
The present study aimed to assess the effect of age and gender on second-grade children’s reading performance. Two hundred and eighty-seven children aged 7.1–8.2 years were divided into two age subgroups (the younger, 85–91 months and the older, 92–98 months) and were examined in reading accuracy, fluency, and comprehension tasks. Results showed a significant effect of age in reading performance, with the older children having better scores than younger ones for reading fluency, reading comprehension, and the total reading performance. Gender was not found to play an important role in reading performance. The findings are discussed on the ground of functional brain development and the different rates of cerebral maturation.